Information and communication technology as a subject of teacher’s tolerance - Soszyński, Piotr (Granice tolerancji w sztuce i w wychowaniu, 2020)
The article deals with tolerance in the teacher and technology relationship in the context of educational law, obliging the teacher to use ICT in didactics of his own subject. Particular cases of tolerance or intolerance to the provisions of educational law are considered, what may extend the ways of defining the tolerance proposed by Ija Lazari-Pawłowska.